Accumulation of Heme Biosynthetic Intermediates Contributes to the Antibacterial Action of the Metalloid Tellurite - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Morales-Sierra, E; Luraschi-Vargas, R; Cornejo-Leiva, F (Nature Publishing Group, 2017)
The metalloid tellurite is highly toxic to microorganisms. Several mechanisms of action have been proposed, including thiol depletion and generation of hydrogen peroxide and superoxide, but none of them can fully explain its toxicity. Here we use a combination of directed evolution and chemical and biochemical approaches to demonstrate that tellurite inhibits heme biosynthesis, leading to the accumulation of intermediates of this pathway and hydroxyl radical. Unexpectedly, the development of tellurite resistance is accompanied by increased susceptibility to hydrogen peroxide. Furthermore, we show that the heme precursor 5-Aminolevulinic acid, which is used as an antimicrobial agent in photodynamic therapy, potentiates tellurite toxicity. Our results define a mechanism of tellurite toxicity and warrant further research on the potential use of the combination of tellurite and 5-Aminolevulinic acid in antimicrobial therapy. © The Author(s) 2017.